Matter-parity as a residual gauge symmetry: Probing a theory of cosmological dark matter - Alves, Alexandre; Arcadi, Giorgio; Dong, P. V.; Duarte, Laura [UNESP]; Queiroz, Farinaldo S.; Valle, José W.F. (Elsevier, 2017)
We discuss a non-supersymmetric scenario which addresses the origin of the matter-parity symmetry, PM=(−1)3(B−L)+2s, leading to a viable Dirac fermion dark matter candidate. Implications to electroweak precision, muon anomalous magnetic moment, flavor changing interactions, lepton flavor violation, dark matter and collider physics are discussed in detail. We show that this non-supersymmetric model is capable of generating the matter-parity symmetry in agreement with existing data with gripping implications to particle physics and cosmology.